Sulforaphane Inhibits Lipopolysaccharide-Induced Inflammation, Cytotoxicity, Oxidative Stress, and miR-155 Expression and Switches to Mox Phenotype through Activating Extracellular Signal-Regulated Kinase 1/2–Nuclear Factor Erythroid 2-Related Factor 2/Antioxidant Response Element Pathway in Murine Microglial Cells - Eren, Erden; Tufekci, Kemal Ugur; Isci, Kamer Burak; Tastan, Bora; Genc, Kursad; Genc, Sermin (Frontiers in Immunology, 2018)
Sulforaphane (SFN) is a natural product with cytoprotective, anti-inflammatory and antioxidant effects. In this study, we evaluated the mechanisms of its effects on lipopolysaccharide (LPS)-induced cell death, inflammation, oxidative stress, and polarization in murine microglia. We found that SFN protects N9 microglial cells upon LPS induced cell death and suppress LPS- induced levels of secreted pro-inflammatory cytokines, Tumor necrosis factor-alpha (TNF-α), Interleukin-1 beta (IL-1β) and Interleukin-6 (IL-6). SFN is also a potent inducer of redox sensitive transcription factor, nuclear factor erythroid 2-related factor 2 (Nrf2), which is responsible for the transcription of antioxidant, cytoprotective and anti-inflammatory genes. SFN induced translocation of Nrf2 to the nucleus via Extracellular signal–regulated kinase 1/2 (ERK1/2) ERK1/2 pathway activation. siRNA-mediated knockdown study showed that the effects of SFN on LPS-induced Reactive Oxygen Species (ROS), Reactive Nitrogen Species (RNS) and pro-inflammatory cytokine production and cell death are partly Nrf2-dependent. Mox phenotype is a novel microglial phenotype that has roles in oxidative stress responses. Our results suggested that SFN induced the Mox phenotype in murine microglia through Nrf2 pathway. SFN also alleviated LPS induced expression of inflammatory microRNA, mir-155. Finally, SFN inhibits microglia-mediated neurotoxicity as demonstrated by conditioned medium and co-culture experiments. In conclusion, SFN exerts protective effects on microglia and modulates the microglial activation state.